Basis Ketahanan Pangan Keluarga di Desa Candirejo Kecamatan Semanu Kabupaten Gunungkidul Daerah Istimewa Yogyakarta - Pramono, Suryo Adi (Jurnal Atma Inovasia, 2021)
Abstract — A relationship between nutritional status and food intake which raises new issues related to the condition of family food security, especially in Candirejo Village (Desa Candirejo, Kecamatan Semanu, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta). The general purpose of community service is to find out what activities or programs can be carried out as a form of maintaining and strengthening family food security, especially in rural areas in order to assist the community in meeting one of the primary needs in the form of food. This service is also carried out to contribute through indirect observation techniques and qualitative data analysis. Data in the form of secondary data obtained from digital platforms / literature studies; website, government publications, internal village records and journals. The role of the village government in maintaining and strengthening family food security will certainly make a significant difference. The existence of social service activities and counseling certainly can help residents to improve skills and abilities that can be applied to villagers in their daily life.Keywords — food security, family, village.  Abstrak — Ada suatu hubungan antara status gizi dan asupan pangan memunculkan isu baru terkait kondisi ketahanan pangan keluarga, terutama di Desa Candirejo, Kecamatan Semanu, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta. Tujuan umum pengabdian adalah untuk mengetahui kegiatan atau program apa saja yang dapat dilakukan sebagai bentuk menjaga dan memperkuat ketahanan pangan keluarga khususnya di daerah pedesaan guna membantu masyarakat dalam pemenuhan salah satu kebutuhan primer berupa pangan. Pengabdian ini dilakukan juga untuk memberikan sumbangsih melalui teknik observasi tidak langsung dan analisis data secara kualitatif. Data-data berupa data sekunder diperoleh dari digital platform/studi literatur; situs website, publikasi pemerintah, catatan internal desa dan jurnal-jurnal. Peran pemerintah desa dalam menjaga dan memperkuat ketahanan pangan keluarga tentu akan memberi perubahan yang signifikan. Adanya kegiatan bakti sosial dan penyuluhan pun tentu dapat membantu warga untuk meningkatkan skill dan kemampuan yang dapat diterapkan bagi warga desa dalam kehidupan sehari-hari.Kata Kunci—Ketahanan pangan, keluarga, desa.